KAJIAN BISNIS SOSIAL PEDAGANG PERANTARA DALAM UPAYA PENGEMBANGAN HORTIKULTURA DI JAWA BARAT (Jurnal Social Economic of Agriculture, 2012)
Currently, 90% of Indonesian small scale agribusiness actors arebeing faced to the global market era. They are also facing a fast growthrate of global market and the market segmentation phenomenon whichexpects positive changes and adaptations in the agricultural supply chain.The method that used in this study is case study. The study location wasbeing selected based on its potential of horticulture product.The study showed that currently the traders have changed theirbusiness pattern from a pure business to a business which relies more onthe partnership with the farmers. This phenomenon was being emerged bythe consumer demand which expects the continuity of supply.From the Social Business aspect point of view, generally thetraders do the partnership system because of their needs of continuity ofsupply from the farmers, not based on helping the farmers. The result ofweighting showed the total score placed between 28-32,5 which means itcan be categorized as a semi-social business.Overall, the study showed that currently the changes are happeningin the traders business pattern, thus, it gives hopes to the agriculturaldevelopment in Indonesia especially for horticulture products of smallscale stakeholders.Keywords: Global market, traders, horticulture, social business.